Estrutura de prática e esforço cognitivo: um estudo eletroencefalográfico - Natalia Lelis Torres (2017)
The way that practice is ordered can influence in motor learning. Explanatory hypotheses proposed in behavioral studies assumed that less repetitive practice schedules, such as random practice, seem to demand greater cognitive effort than more repetitive types of practice organization such as constant and blocked practice. All of these hypotheses emphasize the enhanced demand to memory processes promoted by the less repetitive practice schedules. The present study had as a purpose to investigate if the cognitive effort level involved in random practice schedule is greater than in constant one with an electrophysiological approach. Participated in the study twenty-one undergraduate males, high handed, novice in the task (24,09 ± 4,04 years).The task was consisted in to type a sequence on the numeric keyboard with predetermined relative timing and absolute timing. Participants completed sixty trials in constant practice schedule (only an absolute timing goal) and sixty trials in random practice schedule (three absolute timing goals) and had their cortical electric activity recorded by an electroencephalography (EEG) apparatus throughout practice. Two electroencephalography (EEG) based measures of cognitive states were used: (a) EEG-engagement index, that it is related to sensory processing and attention resources, and (b) EEG-workload indexes, that it is related to working memory load. The motor performance was measure by relative and absolute errors. Students t test and Two-way ANOVAs were conducted on statistics analysis. The results showed that random practice induced greater cognitive effort than constant practice when task engagement was analyzed. Throughout practice, both task engagement and mental workload decreased more in the constant practice condition than in random practice condition. There were greater relative and absolute errors for random practice during the motor skill acquisition. These findings show that the greater cognitive effort demanded by random practice was due to an increased demand for sensory processing opening a novel field of study in practice organization